Spinal cytochrome P450c17 plays a key role in the development of neuropathic mechanical allodynia: Involvement of astrocyte sigma-1 receptors - Choi, Sheu-Ran; Roh, Dae-Hyun; Yoon, Seo-Yeon; Choi, Hoon-Seong; Kang, Suk-Yun; Han, Ho-Jae; Beitz, Alvin J.; Lee, Jang-Hern (PERGAMON-ELSEVIER SCIENCE LTD, 2019)
While evidence indicates that sigma-1 receptors (Sig-1Rs) play an important role in the induction of peripheral neuropathic pain, there is limited understanding of the role that the neurosteroidogenic enzymes, which produce Sig-1R endogenous ligands, play during the development of neuropathic pain. We examined whether sciatic nerve injury upregulates the neurosteroidogenic enzymes, cytochrome P450c17 and 3 beta-hydroxysteroid dehydrogenase (3 beta-HSD), which modulate the expression and/or activation of Sig-1Rs leading to the development of peripheral neuropathic pain. Chronic constriction injury (CCI) of the sciatic nerve induced a significant increase in the expression of P450c17, but not 3 beta-HSD, in the ipsilateral lumbar spinal cord dorsal horn at postoperative day 3. Intrathecal administration of the P450c17 inhibitor, ketoconazole during the induction phase of neuropathic pain (day 0 to day 3 post-surgery) significantly reduced the development of mechanical allodynia and thermal hyperalgesia in the ipsilateral hind paw. However, administration of the 3 beta-HSD inhibitor, trilostane had no effect on the development of neuropathic pain. Sciatic nerve injury increased astrocyte Sig-1R expression as well as dissociation of Sig-1Rs from BiP in the spinal cord. These increases were suppressed by administration of ketoconazole, but not by administration of trilostane. Co-administration of the Sig-1R agonist, PRE084 restored the development of mechanical allodynia originally suppressed by the ketoconazole administration. However, ketoconazole-induced inhibition of thermal hyperalgesia was not affected by co-administration of PRE084. Collectively these results demonstrate that early activation of P450c17 modulates the expression and activation of astrocyte Sig-1Rs, ultimately contributing to the development of mechanical allodynia induced by peripheral nerve injury.
Keywords: PAIN HYPERSENSITIVITY; MOUSE MODEL; DEHYDROEPIANDROSTERONE; RAT; PHOSPHORYLATION; NEUROSTEROIDS; BIOSYNTHESIS; EXPRESSION; INDUCTION; STEROIDS